Finite Element Analysis for Five Transmission Lines in Multilayer Dielectric Media - Sarhan Musa; Matthew N. O. Sadiku (Institute of Advanced Engineering and Science, 2012)
Development of very high speed integrated circuits is currently of great interests for today technologies. This paper presents the quasi-TEM approach for the accurate parameters extraction of multiconductor transmission lines interconnect in single, two, and three-layered dielectric region using the finite element method (FEM). We illustrate that FEM is as accurate and effective for modeling multilayered multiconductor transmission lines in strongly inhomogeneous media. We mainly focus on designing of five-conductor transmission lines embedded in single-, two-, three-, and four-layered dielectric media. We compute the capacitance matrices for these configurations. Also, we determine the quasi-TEM spectral for the potential distribution of the multiconductor transmission lines in multilayer dielectric media.